Entrepreneurial orientation and market orientation as drivers of Micro Small Medium Entrepises (MSMEs') Performance - Dunga Dwi Barinta; Siti Aisjah; Christin Susilowati (Journal of Business and Management Review, 2022)
Micro, Small and Medium Enterprises (MSMEs) contribute to the Gross National Income (GDP) up to 40% and the creation of new job vacancies. Based on 25% of the total number of MSMEs in Indonesia cannot produce during the pandemic. In addition, internal problems such as lack of business knowledge, IT updates, low understanding in market make most MSMEs have low firm performance. Firm performance is an important part of a company to observe and evaluate the suitability of the results in business activities with the predetermined plan. Some researchers believe that firm performance is affected by Entrepreneurial Orientation and Market Orientation. This research was conducted by MSMEs that run their businesses in Malang City, East Java Indonesia. Data collection uses non-probability method approach with simple random sampling technique. The number of respondents collected in this study amounted to 112 respondents, but which can be used in data processing was amounted to 101 respondents. The method of data analysis uses SEM (Structural Equation Modeling) based on Partial Least Square (PLS) using SmartPLS 3.3 software application. This study aims to investigate the role of Entrepreneurial Orientation and Market Orientation in improving the performance of MSMEs. The research findings that entrepreneur orientation and market orientation are proven to have an effect on improving the performance of MSMEs. However, entrepreneur orientation cannot have a direct impact on improving performance. Entrepreneur orientation must be supported by market orientation in improving MSME performance